TOWARDS THE QUESTION OF SOCIO-CULTURAL AND EPISTEMOLOGICAL STATUS OF IDEOLOGY IN CONTEMPORARY SOCIETY - V. E. Gromov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. To consider the subjective factor of cultural and historical identity of society as an ideology, without which the positive social and personal development is inconceivable. To produce proofs against the false rhetoric about “deideologization”, as a harmful and destructive idea for social awareness, that aims to destroy basic humans’ ethical values and to manipulate their living motivations. Methodology. The method of investigation of the problem was indicated as analytical result of preliminary scheme that was directed by the author towards the realization of his conception. This subjectivism of thinking “on one’s own account” (K. Jaspers) and “without relying on existences” (M. Heidegger) the author attempted to corroborate with notions of modern scientists about the relations of causes in non-linear systems. Scientific novelty. It would be difficult to talk about scientific novelty if we had no thought on “chronic” issues of contemporary society and its world outlook vectors. It is possible to talk about the existential newness, the rise of personal indifference in connection with the irresponsible short-sightedness with which today under the guise of democratic overcome the totalitarian narratives is lightly questioned the universally valid moral values, belittled the philosophical classics and dragged the false ideological omnivorous freedom and devaluation of high culture. Conclusions. Personal life of individuals and historical results of their vital activity are dependent on their world outlook orientation. Human being without ideology is similar to lost creature with weakened will and uncertain conscience. The problem is not in refutation of ideology, but in its production and selection. It’s impossible to build ideal social relation based on ideal principles, but in the same time it is impossible to imagine social development without any general orientation. Man can create only ruin and prepare himself for apocalypse without the culture, which would be reflection of philosophical understanding and orientation.